MERAMALKAN (FORCASTING) PERKEMBANGAN IHSG MENGGUNAKAN TEKNIK BOX-JENKINS - Herry Yulistiyono; Shanty Oktavilia (Trunojoyo University of Madura, 2007)
Indeks Harga saham Gabungan (ISHG) growth is one of the stock exchange and economic stability level indicator. It was Proved on the crisis era which happen in indonesia since mid 1997, IHSG often become decision making refence in the business field to determine the policy stept. So, the IHSG forecasting is higly needed especially to the exchange market player and the other economic player.this article try to set forth Indeks Harga Saham Gabung Forecast technique on Jakarta Stock Exchange on the period of 1996 to 2002 with ARIMA Box Jenkins method, is short period forecast technical base on the data time series.